The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/toxins13010022
|View full text |Cite
|
Sign up to set email alerts
|

The Extreme Ends of the Treatment Response Spectrum to Botulinum Toxin in Cervical Dystonia

Abstract: Background: The response to BoNT is not uniform; a broad spectrum of responses and side-effects usually occurs. This study aimed to show special cervical dystonia cases with therapy response very different to normal treatment course which indicate the extreme ends of therapy spectrum. Patients: Clinical data and course of treatment of five long-term treated patients with cervical dystonia out of therapy response norms are presented: a patient who was supersensitive to standard dose and has required dose adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…This implies that most patients are reinjected well before the clinical effect of the previous injection has fully declined, and that patients experience a “staircase-like” improvement, injection by injection. This phenomenon is presented in detail in [ 23 ]. The outcomes of the present study do not include the analysis of the development of the peak effect at approximately four weeks after injection, but rather a continuous, stable plateau of improvement which is achieved via repeated injections at a fixed interval of 3 months and an analysis of the severity of CD at the end of an injection cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that most patients are reinjected well before the clinical effect of the previous injection has fully declined, and that patients experience a “staircase-like” improvement, injection by injection. This phenomenon is presented in detail in [ 23 ]. The outcomes of the present study do not include the analysis of the development of the peak effect at approximately four weeks after injection, but rather a continuous, stable plateau of improvement which is achieved via repeated injections at a fixed interval of 3 months and an analysis of the severity of CD at the end of an injection cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In a review from 2003, a benefit from BoNT therapy was reported in 70–85% of CD patients [ 25 ]. The long-term outcome from BoNT therapy depends on a variety of factors: the genetic constellation of the patient (see next paragraph), the BoNT preparation used [ 23 , 26 ], the dose per session, the length of the treatment cycle, the clinician’s knowledge about optimal injection sites for muscles (detailed in [ 27 , 28 ]), and the duration of the treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This further emphasizes the necessity for the adaptation of the dose to clinical needs. In a previous paper, we emphasized that in patients with fairly high initial severity (as in the DR subgroup of the present cohort), an unusually high dose may be necessary at the beginning of BoNT therapy to achieve a satisfying response [ 31 ]. If this adaptation is not performed, the risk is high that the patient terminates BoNT therapy and is classified as a primary non-responder [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for discontinuation are poorly understood [ 21 ]. As in children with cerebral palsy (CP) [ 22 ] primary non-response [ 17 , 23 ], disease progression [ 24 , 25 , 26 , 27 ], cost of therapy, inconvenience, side effects and incorrect diagnoses [ 21 , 22 , 28 ] contribute to discontinuation of BoNT therapy in CD. Special types of CD as antecollis are associated with moderate to severe side-effects and high withdrawl rates [ 24 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%